Systemic Epstein-Barr Virus-positive T-Cell Lymphoma of Childhood Presentation With Hemophagocytosis. Issue 4 (May 2019) - Hung, Giun-Yi; Yu, Ting-Yen; Yen, Hsiu-Ju; Yang, Ching-Fen; Lin, Li-Yih; Horng, Jiun-Lin
Abstract : A 2-year-old Asian girl presented to our facility for the evaluation of thrombocytopenia. She was treated with intravenous immunoglobulin under the impression of immune thrombocytopenia. However, her body temperature spiked and progressive pancytopenia, hepatosplenomegaly, abnormal liver function, coagulopathy, and pulmonary infiltration developed. The final diagnosis was systemic Epstein-Barr virus (EBV)-positive T-cell lymphoma of childhood with hemophagocytic syndrome. This type of cancer is extremely rare but occurs more commonly in Asians. Its prognosis is generally poor, and a treatment strategy is yet to be established. Double staining for EBV-encoded RNA and CD3 or CD8 is crucial for diagnosis. This type of lymphoma must be diagnosed differentially from acute EBV-associated hemophagocytic lymphohistiocytosis, which is considered nonmalignant. This case report highlights the importance of awareness of this type of rare cancer, a comprehensive diagnostic approach, and close communication between primary care physicians and pathologists.